A Study on the Impact of COVID-19 on the Income of the General Population in Jaipur, India - Purohit, Pratiksha; Purohit, Tushar; Choudhary, Dr. Satender; Batwal, Priyanka (Journal of Social Science and Humanities, 2024)
The COVID-19 pandemic has emerged as a critical challenge for the current generation. One of its major implications is the adverse impact on the income of the general population. Several studies and reports have documented the significant effect of the pandemic on the earnings of individuals in both formal and informal sectors. Thus, there is an urgent need to investigate the pandemic's impact on various income groups and employment sectors, including government, private, business, professionals, and informal sectors. To explore the consequences of the COVID-19 pandemic on income levels in Jaipur, a research project was conducted. The study encompassed 211 individuals from diverse occupations and income groups to provide a comprehensive understanding of the pandemic's effect on income across different backgrounds and professions. Random sampling technique was used for data collection, and a Google form was employed to design the questionnaire and distribute it to respondents via email. Data collection took place over two months, from January to March 2023. The data collected were analyzed using SPSS software, and a chi-square test was utilized to examine the relationships between different variables. The participants were asked to provide detailed information on how the COVID-19 pandemic has affected their income and work patterns. The study's findings revealed that the impact on different occupations varied and had multiple dimensions. Therefore, policymakers should acknowledge that the pandemic's impact on income levels has not been uniform across different demographics. Consequently, policy responses should be customized to address the specific needs of distinct groups.